Assessment of BSL kω turbulence model for predicting flow characteristics in a solitary wave motion - Winarta, Bambang; Damarnegara, Satria A A N; Nurul Nadrah Aqilah, Tukimat; P. T., Juwono; E., Suhartanto; A. P., Hendrawan; A., Subagiyo (IOP Publishing, 2021)
A deep understanding of boundary layer characteristics under wave motion, especially bottom shear stress on the seabed, is critical in sediment transport calculation and modeling. In this present study, boundary layer characteristics under solitary wave motion over the smooth bed are investigated through the Baseline (BSL) kω model. It will also consider the result of a laboratory experiment performed in a closed conduit generation system. The conclusion said that the BSL kω model can replicate well on horizontal and vertical velocity distribution at Reynolds number (Re) = 2.25 x 105. In addition, a turbulent spike which was occurred during decelerating phases of oscillatory motion can be predicted well also by the BSL kω model at Reynolds number (Re) = 6.06 x 105.